Curiosimusca, gen. nov., and three new species in the family Aulacigastridae from the Oriental Region (Diptera: Opomyzoidea) - Rung, Alessandra; Mathis, Wayne N.; Papp, László (Zootaxa, 2005)
A new genus, Curiosimusca, and three new species (C. khooi, C. orientalis, C. maefangensis) are described from specimens collected in the Oriental Region (Malaysia, Thailand). Curiosimusca is postulated to be the sister group of Aulacigaster Macquart and for the present is the only other genus included in the family Aulacigastridae (Opomyzoidea). Morphological evidence is presented to document our preliminary hypothesis of phylogenetic relationships.